2015
DOI: 10.1002/mds.26371
|View full text |Cite
|
Sign up to set email alerts
|

Advances in clinical trials for movement disorders

Abstract: In the past several years, there have been several innovations in the design of clinical trials assessing new therapies for patients with movement disorders. These include attempts to address difficulties in conducting clinical trials in treated patients in the advanced stages of their illness, demonstrating disease-modifying effects or a reduction in the development of cumulative disability, and assessing the effects of interventions in patients in the premanifest state of their disease. In addition, there ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…20,21 Most notably, rasagiline, which is approved for symptomatic treatment in Parkinson’s disease, showed inconclusive results in a delayed-start study 22 designed to assess effects on disease progression. In our trial, it might be tempting to view persistent benefits detectable after the washout period as evidence of disease modification.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Most notably, rasagiline, which is approved for symptomatic treatment in Parkinson’s disease, showed inconclusive results in a delayed-start study 22 designed to assess effects on disease progression. In our trial, it might be tempting to view persistent benefits detectable after the washout period as evidence of disease modification.…”
Section: Discussionmentioning
confidence: 99%
“…Current evaluation standards in Parkinson's disease (PD), such as the Unified Parkinson's Disease Rating Scale (UPDRS), are very useful, but have important limitations. As recently pointed out, these scales report a semiquantitative and subjective score, nonsensitive to subtle motor changes . In addition, these assessments typically require the patient to travel to the clinic, and they need to be performed by a trained specialist, representing an additional burden for the patient and hence being time and cost consuming.…”
mentioning
confidence: 99%
“…As recently pointed out, these scales report a semiquantitative and subjective score, nonsensitive to subtle motor changes. [2][3][4] In addition, these assessments typically require the patient to travel to the clinic, and they need to be performed by a trained specialist, representing an additional burden for the patient and hence being time and cost consuming.…”
mentioning
confidence: 99%
“…Newly available, high quality evidence can be incorporated into the study design allowing for alteration of sample size based on observed variability, modifying ineffective doses, moving patients among various trial phases, or simply ending a trial early due to failure of efficacy (such as in the case of NET-PD and PRECEPT studies [47,48]). Although these designs can improve efficiency and reduce drug development time, they may introduce bias, require complex operational support from statisticians and safety monitoring boards in order to make real time decisions based on current data [2,49]. Additionally, in both futility and adaptive designs, characterising a response as "positive" or "negative" in a relatively short time period in a such a slowly progressive condition as PD can be challenging.…”
Section: Clinical Trial Designmentioning
confidence: 99%
“…However, "structural errors" pertaining to inadequate trial design, selection of inappropriate endpoints, poor patient selection, or mishandling of missing data, can be minimised and increase the chance of detecting true disease modifying effects [2,3]. This review will consider methodological issues relating to detecting efficacy in disease modification phase III trials and suggest future directions that are being explored that may improve the ability to detect any signal of effect.…”
mentioning
confidence: 99%